Indoleacetic Acid Oxidase Activity in Heterotrophic and Autotrophic (Habituated)Tobacco Callus Tissues - Szabo, M.; Tari, I.; Koves, E.
Activity of indoleacetic acid oxidase (IAA oxidase)was compared in auxin autotrophic and hetero· trophic tobacco callus tissues. Auxin heterotrophic callus grown on auxin-free medum possessed the highest auxin decomposing ability. Autotrophic callus tissue had a minimum activity while the enzyme activity of heterotrophic one was half of the level of the former one. It appears, there is no direct correspondence between the auxin heterotrophy and increased IAA destructive capacity of the tissues.
Keywords: IAA OXIDASE; AUXIN AUTOTROPHY AND HETEROTROPHY; CALLUS CULTURE; NICOTIANA TABACUM; AUXIN AUTOTROPHY AND HETEROTROPHY; CALLUS CULTURE; NICOTIANA TABACUM